Avaliação do número e posição de frutos de melancia produzidos em ambiente protegido - Seabra Júnior, Santino [UNESP]; Pantano, Sílvio C. [UNESP]; Hidalgo, Ari F. [UNESP]; Rangel, Maurício G. [UNESP]; Cardoso, Antonio I.i. [UNESP] (Associação Brasileira de Horticultura, 2003)
The fruit production of watermelon, cultivar New Kodama, grown in two positions along the stem (8th-11th node and 13th-16th node), with one or two fruits per position was evaluated, under protected cultivation. The experiment was performed in Botucatu, São Paulo State, Brazil, from October to December, 2000. The total fruit production (kg/plant), the average fruit weight (kg/fruit) and the total soluble solids were evaluated. When only one fruit was allowed to grow between the 8th and 11th node, total fruit production was lower (2,04 kg/plant) than keeping two fruits (2,57 kg/fruit). However, the fruit production was similar (2,0 kg/plant) to one or two fruits when they were allowed to grow between the 13th and 16th node. The average fruit weight (2,05 kg/fruit) and total soluble solids (8,78ºbrix) were higher in fruits grown from plants with only one fruit, than two fruits per plant. Total soluble solids were also higher in fruits grown from 8th to 11th (8,21ºbrix) node position.

Estudou-se a produção de melancia, cultivar New Kodama, avaliando 1 ou 2 frutos por planta fixados nos ramos entre o 8º e 11º nó e 1 ou 2 frutos por planta fixados nos ramos entre o 13º e 16º nó, no sistema tutorado em ambiente protegido. O experimento foi conduzido na UNESP, em Botucatu (SP), de outubro a dezembro de 2000. Avaliou-se a produção total de frutos por planta, peso médio de frutos e teor em sólidos solúveis totais (ºbrix). A produção foi menor (2,04 kg/planta) quando manteve-se apenas um fruto fixado do 8º ao 11º nó, do que quando manteve-se dois frutos (2,57 kg/planta), mas não houve diferença significativa quando manteve-se um ou dois frutos fixados do 13º ao 16º nó, produzindo cerca de 2 kg por planta. Observou-se também maior peso médio de frutos (2,05 kg/fruto) e maior teor de sólidos solúveis totais (8,78ºbrix) quando mantidos apenas um fruto por planta e maior teor de sólidos solúveis totais (8,21ºbrix) nos frutos mantidos do 8º ao 11º nó.
Evaluation of the number and position of watermelon fruits cultivated in a greenhouse
Keywords: Citrullus lanatus; pruning; rough-hewing; protected cultivation; fruit production; Citrullus lanatus; poda; raleio; cultivo protegido; produção de frutos